Brazil’s Primary Care Strategy - Couttolenc, Bernard (World Bank, Washington, DC, 2013)
This case study summarizes the responses to the questionnaire on The Nuts and Bolts of the Program Expanding Health Coverage to the Poor, developed within the framework of the World Bank's UNICO - Universal Challenge Program. By so doing, it assesses the key features and the achievements and challenges of Brazil s Primary Care Strategy (PCS) and analyzes the contribution of this strategy to the establishment and implementation of universal coverage. Section 2 provides context for the discussion by summarizing key reforms and the impact of the PCS and describes Brazil s health care delivery and financing system. The institutional architecture and interaction of the health care program (HCP), in this case the PCS, is discussed in section 3. Sections 4 through 8 outline the main features of the strategy, including the identification and targeting of beneficiaries, management of public funds, services covered, and the information environment. The case study concludes with a discussion of lessons learned (section 9) and the pending agenda (section 10).